The Relationship Between Self-Confidence and Social Interaction in Adolescents from Divorced Families in Manado City - Zefanya Jennifer Lasut; Ratriana Yuliastuti Endang Kusumiati (Jurnal Indonesia Sosial Sains, 2024)
A broken home is a family condition that experiences a split due to a problem that results in quarrels about divorce. A broken home greatly impacts the process of child development in social interaction. Children, especially in adolescence, are an important segment of life in the individual development cycle and require interaction with others in the process of self-discovery, so self-confidence is needed. This study aims to determine the relationship between self-confidence and social interaction in adolescents from divorced families. Participants in this study were 77 adolescents from divorced families in Manado City with an age range of 13–18 years. The sampling technique used in this study was purposive sampling. Data were collected using the self-confidence scale compiled by Lauster (2012) and the social interaction scale developed by Winslow et al.. The results of this study showed a significant positive relationship between self-confidence and social interaction, with a correlation of r = 0.477 and a significance of 0.000 (p<0.05). This means that the higher the self-confidence, the higher the social interaction.